Jakość powietrza w wybranych województwach w Polsce - Stelęgowski, Artur (Lodz University of Technology. Faculty of Civil Engineering, Architecture and Environmental Engineering, 2019)
Jakość powietrza zależy od charakterystyki obszaru, na którym jest badana. Tereny zamieszkane, takie jak: wsie, małe i średnie miasta oraz duże miasta, są szczególnie narażone na niekorzystny wpływ emisji zanieczyszczeń ze źródeł takich jak energetyka zawodowa czy transport drogowy. W celu oceny stanu jakości powietrza na terenie miast i wsi w Polsce, przeanalizowano dane z pięciu lat, z pięciu wybranych województw, czyli: Dolnego Śląska, Wielkopolski, województwa łódzkiego, Mazowsza, oraz województwa lubelskiego.

The air quality depends on the characteristics of the analyzed area. Inhabitable areas, such as villages, small and medium towns, and large cities, are particularly exposed to the adverse impact of pollution emissions from sources such as power industry and road transport. In order to assess the state of air quality in cities and villages in Poland, the data from 5-year measurements, from five selected voivodeships (Lower Silesia, Greater Poland, Lodz, Mazovia, and Lublin), were analyzed.